La rage d'écrire, ou, Le défi féminin dans l'oeuvre de Nicole Brossard - Delepoulle, Anne-Marie (Université de Paris-Val de Marne, 1983)
Keywords: amériques; arts; discipline; mémoires/thèses; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

La Québécoite: roman - Robin, Régine (Collection Littérature d'Amérique, 1983)
Sous le regard de l'Autre. Par l'auteure d'Histoire et linguistique (Colin, 1973) et d'une étude sur l'écriture juive (Le Sorbier, 1983), un récit dans lequel ce professeur d'université française, d'origine judéo-russe, qui enseigna à Montréal, Laval et Sherbrooke relate, pour le bénéfice de ses étudiants, l'histoire de sa découverte du Québec entre 1974 et 1981. Régine Robin, de formation marxiste, manifeste une attention particulière aux luttes ouvrières (grèves, etc.), politiques, idéologiques. L'éditeur parle avec justesse d'un livre d'émigrante sur l'exil, la langue et la vie d'ici. Composition en mosaïque. Inventaires, comparaisons, fragments, altérités.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; arts; cours; discipline; disicpline; histoire et politique; immigration; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"--
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

In search of our mothers' gardens womanist prose - Walker, Alice (Harcourt Brace, 1983)
In this, her first collection of nonfiction, Alice Walker speaks out as a black woman, writer, mother, and feminist. Among the thirty-six pieces are essays about other writers, accounts of the civil rights movement of the 1960s and the anti-nuclear movement of the 1980s, and a vivid memoir of a scarring childhood injury and her daughter’s healing words.
Keywords: 1900-1999; amériques; approches et analyses; arts; cours; cycles supérieurs; discipline; droits civiques; fem1000; fem3300; fem7000; histoire et politique; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; thématiques; womanist; états-unis; études littéraires